Listening to hindustani music - Chetan Karnani; KARNANI (Chetan) (Bombay: Sangam Books, 1976)
Based on the author's book: Listening to Hindustani music (1976), with revisions and additions on the music of South India, Karnatic music, Gharanas, and Hindustani instrumentalists.
Keywords: Hindustani Vocalists; Hindustani Instrumentalists